THE EFFECT OF PECHA KUCHA METHOD TOWARDS STUDENTS’ SPEAKING SKILLS AT THE ELEVENTH GRADE OF SMAN 10 PANDEGLANG IN THE ACADEMIC YEAR 2025/2026 - Diya Rahma Fadila; Rizdki Elang Gumelar; Nur Azmi Rohimajaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to investigate the effect of using the Pecha Kucha method (independent variable) on students’ speaking skills (dependent variable) in the eleventh grade of SMAN 10 Pandeglang in the academic year 2025/2026. The research employed a quantitative approach with a quasi-experimental design. The population consisted of all eleventh-grade students, while the sample was selected using cluster random sampling, resulting in 60 students equally divided into the experimental class (XI-1) and the control class (XI-4). The research instrument was a speaking test covering five aspects: fluency, vocabulary, grammar, pronunciation, and comprehension, which had been tested for validity and reliability prior to use. The study was conducted over four meetings, including a pre-test, treatment, and post-test. In the experimental class, the pre-test scores ranged from 32 to 64 with a mean of 44.13 and a standard deviation of 9.066, while the post-test scores ranged from 40 to 96 with a mean of 68.13 and a standard deviation of 12.539. In the control class, the pre-test scores ranged from 32 to 60 with a mean of 43.60 and a standard deviation of 7.600, whereas the post-test scores ranged from 44 to 88 with a mean of 59.60 and a standard deviation of 9.705. The findings indicate that the Pecha Kucha method has a significant positive effect on students’ speaking skills. Therefore, this method is recommended as an alternative strategy in teaching speaking, as it can improve students’ fluency, vocabulary, grammar, pronunciation, and comprehension in a structured and engaging manner.